Pelatihan dan Pendampingan Pengelolaan Berkas Klaim BPJS Kesehatan untuk Menurunkan Angka Pending Klaim Rawat Jalan di Rumah Sakit Umum X - Mulyana, Mulyana; Situmorang, Masriani; Zhahara, Jihhan Naailah; Hasibuan, Rifdah Salsabila; Erika, Nur; Afrida, Aliya (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2026)
BPJS Health claims are one of the main sources of funding for hospitals, which are highly dependent on the accuracy and completeness of claim files. A common problem is the high number of pending claims or claim files returned by BPJS Health due to administrative discrepancies, incorrect diagnosis and procedure coding, and incomplete supporting documents. This community service activity aims to improve the competence of casemix and medical record officers through training and mentoring in managing BPJS Health claims in order to reduce the number of pending outpatient claims at General Hospital X. The activity was carried out in stages: preparation, training and mentoring, and evaluation. The evaluation was conducted by measuring staff understanding through pre-tests and post-tests and comparing the percentage of pending claims before and after the community service activity. The results of the activity showed an increase in the average understanding score of officers from 62.5 to 86.3 and a decrease in the percentage of pending claims from 21.4% to 11.2% during the evaluation period. These findings indicate that training and mentoring in managing BPJS Kesehatan claims have a positive impact on partners and are recommended to be implemented continuously to maintain the quality of claim management in hospitals.